Integrating Tradition and Modernity: The Gharana System for Effective Mentorship at GAIMS (GAIMS Journal of Medical Sciences, 2025)
This editorial highlights the key features and benefits of the GAIMS Gharana System, an innovative and a unique blend of ancient traditions of knowledge and modern mentoring practices.